Effect of soybean leaf trichomes on the preference of various soybean pests on field. Issue 1 (March 2021) - Faiz, M F; Hidayat, P; Winasa, I W; Guntoro, D
Abstract: Trichomes as morphological characteristics of soybean plants can affect the behaviour of some insect pests. Insect behaviour can be affected positively, negatively, or neutral by trichomes character depending on the insect species. This research is aiming to know the effect of soybean leaf trichome density on various species of soybean pest population dynamics using five local varieties from Indonesia ('Anjasmoro', 'Argomulyo', 'Dena-1', 'Grobogan', and 'Devon-1'). In this research, the pest population on the field was observed by active observation method on the five different soybean varieties every once a week that also treated with corn plant and Crotalaria juncea around plots as barrier plant and refugia plant (with and without barrier plant). The result indicates that a higher number of abaxial leaves trichome density has a negative effect on Empoasca sp. population, which is the opposite of the effect known given to Bemisia tabaci . The leaf trichome density does not have a distinctive impact on aphid, herbivorous orthopteran, and various lepidopteran foliage-feeders founded on the field. This research result may provide information related to additional alternatives for pest management using plant physical traits to enhance plant resistance and encouraging the use of integrated pest management.